TECHNOLOGICAL DEGRADATION OF SHAFT SURFACE DURING MACHING (Perner's Contacts, 2014)
The paper deals with identifying the causes of surface failure of a shaft made of material 42CrMoS4. On the basis of microstructural analysis completed by hardness testing, the occurrence of undesirable phases, such as non-metallic inclusions in the structure of the shaft, can be demonstrated. In the presence of various heterogeneous phases in the material structure, plucking of particles can occur during chip machining which leads to surface damage. In the conclusion, the authors recommend checking the starting material, which can eliminate problems that cause the degradation of the surface of the shaft. The failure of the surface causes the notch effect which initiates further failures of the material.
Keywords: machining; defects; non-metallic inclusions; microstructure; hardness; cracks